Motivations and obstacles to goat meat consumption willingness: exploring influencing factors related to consumer habits and awareness - Brahim Hamad; Leyla Hadef; Meriem Bellabidi (Cogent Food & Agriculture)
The purpose of this study was to identify the main motivation and barrier factors to the consumption of goat meat as well as evaluate the impact of consumer habits and awareness on willingness to eat this meat. 240 randomly selected consumers from the El Oued region in south-east Algeria were given organised, independently managed surveys. The top three reasons why satisfied survey participants (202 consumers) chose to consume goat meat were its flavour (35.1%), low fat level (30.2%), and health advantages (23.3%). The most significant barriers to the consumption of this meat for the 38 dissatisfied consumers were, concurrently, its flavour and aroma, with percentages of 57.9% and 26.3%, respectively. The greatest significant effect on consumption willingness was found to be the frequency of consumption (p < 0.001). Knowledge of cooking techniques and nutritional advantages also had a significant positive relationship (p < 0.05). The consumption of goat meat was more closely connected by the survey participants (p < 0.05) with stewing techniques than with grilled methods. The sensory factors behind consumer decisions also substantially affected the intake of goat meat (p < 0.05). Overall, an organised and planned strategy to market goat meat as a nutritious food, increase knowledge of its unique qualities, and increase exposure and communication about its preparation techniques might increase consumer demand for it.